A Review on IoT Based Vehicular Edge Computing - Narayan Mohanty, Mihir (International Journal of Psychosocial Rehabilitation, 2025)
Vehicular Edge Computing (VEC), a brand new network paradigm, has recently been introduced in the brand new system to further strengthen its storage for computing. The obstacle to compliance with certain computational and communications specifications is prominent along with the beginning of modern vehicular applications. With all the success of VEC, the sponsoring services of the service provider close to both smart automobiles, such as lowering latency and improving the high-level quality of service (QoS). The VEC structure combined with every notion of software, its own services and the automobile, is exemplified by this paper. This paper have assessed and described all the most recent and relevant solutions. This paper nail forward research problems and discard slightly. This paper enables readers to gain a better understanding of the field, but it also provides guidance for one area of research within the VEC.